An approximate analytical solution of a filtration problem - Kolos, I.V.; Kolos, M.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2008)
An analytical expression to determine an approximate value of the impulse transition matrix for an admissible filter is obtained for the problem of linear optimal filtration with degenerate white noise. Keywords: transition matrix, filtration problem, optimal filtration, degenerate noise, white noise